Mengeksplorasi Tantangan Guru dalam Menerapkan Pembelajaran Diferensiasi di Sekolah Menengah Atas - Ningsih, Ratna; Pusparini, Ririn (STKIP Siliwangi, 2024)
This research explores the challenges faced by English teacher in implementing differentiated learning methods, particularly in speaking skills and investigates the solutions toward the problems. The study uses a qualitative method with case study design. As it was employed to describe the experiences of an English teacher at a high school in Surabaya who applied the differentiation learning method. The respondent of this research is an English teacher who is employing differentiated learning. This research used interviews and observations to collect the data. The results showed that the teacher faced several challenges in using differentiated learning in teaching speaking. The challenges are selecting content that suits students' level ability, managing passive students, and dealing with students with confidence, anxiety, and vocabulary and grammar issues as a product of learning. The learning environment also presents challenges, such as noise and classroom facilities. In addition, the data also revealed that teacher found solutions toward the problems, such as providing multiple texts, allowing active students to speak in turns, offering design products based on negotiation, and calming the class to maintain concentration. These solutions have made students comfortable in learning, as they are tailored to their skills, character, learning styles, and needs.